Need analysis of English language usage for Tourism university students - Mochammad Musafa'ul Anam; Aprilia Rachmadian (Universitas Merdeka Malang, 2020)
There are 5 fundamental competencies that need to be acquired by all labors in tourism industry, one of them is communication. As an international language, English is still be chosen as a tool for communicating, negotiating, and interacting between laborers as well as customers or tourists. Thus, the development of English communication needs to be seemed as a mandatory thing for any tourism student, just before he/she is being involved in the real tourism sector. Need analysis is required. This is a Need Analysis study that generally employs a quantitative approach. A questionnaire was used to collect data in which the questionnaire was divided into two categories, 8 questions were formed as a checklist where 14 others were formed as 5 rating Linkert-scale questions. Mean and Standard Deviation were employed to calculate the need of English skills by tourism students. Whereas, Standard Deviation (SD) was employed to calculate the distribution of the scores gained by the respondents. Frequency (f) and percentage (%) were used to calculate the functions and problems of English usage by students in the tourism sector. The result shows that all language skills in English are needed for tourism students. Yet, in order to achieve the goal of providing an excellent service to tourists, it will need a well-prepared program and syllabus that may employ the internet as a source of information since the internet was the most popular reading source for tourism students. Keyword: English skills development, need analysis, Tourism university students DOI: 10.26905/enjourme.v5i2.5105